Analisis Kontaminasi DNA Babi (Sus scrofa domesticus) Pada Produk Olahan Bakso Sapi Dan Ayam di Tuntungan, Sumatera Utara - Sandika , Febri; Idami, Zahratul; Idris, Muhammad (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Meatballs are a popular processed meat product in Indonesia. High consumption of meatballs is accompanied by increasing public concern, especially among Muslims, regarding the halal aspect of the product. The potential contamination of pork DNA (Sus scrofa domesticus) in beef and chicken meatballs is a critical issue, whether due to unintentional cross-contamination or adulteration. Tuntungan area, North Sumatra, with its diverse demographic and trading characteristics, is an important location to assess the level of contamination. Objective: This study aimed to detect the presence of pork DNA (Sus scrofa domesticus) contamination in processed beef and chicken meatball products traded in the Tuntungan area, North Sumatra. Methods: Four meatball samples (three chicken meatballs and one beef meatball) were collected from street vendors and meatball stalls at different locations. DNA detection was performed molecularly using the Real-Time Polymerase Chain Reaction (qPCR) method with the *Genechecker UF-300* instrument. The procedure began with sample preparation, DNA extraction using the Genolution tool, master mix preparation, and analysis using the PCR Gen Checker chip. Result validation was based on the Cycle threshold (Ct) value in the target channel (FAM for pork DNA) and the internal control channel (ROX). Results: The analysis results of all four samples showed a FAM Ct value of 0 (not detected), indicating no amplification of specific pork target DNA. Meanwhile, the ROX Ct value (internal control) in all samples was detected in the range of 19.41–20.50, proving that the DNA extraction and amplification process ran optimally without inhibition. The positive control showed valid amplification signals, and the negative control showed no contamination. Conclusion: Based on the molecular detection results, it can be concluded that all tested beef and chicken meatball samples from the Tuntungan area were not contaminated with pork DNA (Sus scrofa domesticus). This finding indicates that traders in the area have applied good processing practices and separated raw materials, so the meatballs sold meet the halal aspect in terms of ingredient authenticity.